Volumetric and Viscometric Studies of Binary Mixtures of Ethyl Acetate with n-Propanol and 2-Propanol at T= (303.15, 308.15, 313.15, and 318.15) K under Atmospheric Pressure (Journal of Scientific Research, 2025)
In this study, densities and viscosities of binary mixtures formed by ethyl acetate with n-propanol and 2-propanol have been measured over the entire range of composition at T = (303.15, 308.15, 313.15, and 318.15) K under atmospheric pressure. Excess molar volume, VE, deviation in viscosity,    and excess Gibb’s free energy of activation of viscous flow,  have been calculated from experimental density and viscosity data. The computed excess functions have been fitted to Redlich-Kister polynomial equation. The observed values of excess properties for both the systems have been interpreted in terms of molecular interaction in the mixtures. Results show that for both mixtures, the chemical or specific interactions between ethyl acetate and alcohol molecules are absent, and dispersion type forces are predominant.